New protocol of dioxins analysis in human blood - Todaka, Takashi; Hirakawa, Hironori; Tobiihi, Kazuhiro; Iida, Takao (Fukuoka igaku zasshi = Hukuoka acta medica, 2003)
We developed a new analytical method for accurately determining concentrations of polychlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs) and non-ortho-coplanar polychlorinated biphenyls (Co-PCBs) at a blood volume of 5 g. The method consists of three major steps, the extraction of lipid from human blood by an accelerate solvent extractor (ASE) system, a clean-up procedure at a scale one-fourth that of the conventional method, and a sensitive determination method by a high-resolution gas chromatography/high-resolution mass spectrometry (HRGC/HRMS) equipped with a solvent cut large volume (SCLV) injection system as a large volume injection technique. By the improvement of the pretreatment method, the operation time and consumption of the solvent could be drastically reduced, and the sensitivity of the GC-MS with the SCLV injection system was increased to 10 times the level of the classical method. From the results of the PCDDs, PCDFs and Co-PCBs concentrations measured by the developed method and the conventional method using the same blood sample, it was confirmed that the measurement became possible at a blood volume of 5 g. The developed method is more effective than the conventional method for treating many samples within a short period of time with high reproducibility.